2009
DOI: 10.1177/1403494809340494
|View full text |Cite
|
Sign up to set email alerts
|

Work life and mental wellbeing of single and non-single working mothers in Scandinavia

Abstract: This study suggests that the Scandinavian welfare democracies have not yet been successful in relieving the financial pressure experienced by single working mothers. Development of efficient financial support systems should be prioritized. Ways to reduce work-family conflict in both single and non-single mothers in Scandinavia should also be given increased attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 23 publications
1
51
0
3
Order By: Relevance
“…However, little is known about levels and predictors of mental well-being in various groups of employed mothers. A recent study by the author of the present paper assessed levels and predictors of mental well-being in samples of single and coupled employed mothers in Scandinavia (7). Coupled mothers reported higher levels of mental well-being and lower levels of financial hardship than single mothers.…”
Section: Introductionmentioning
confidence: 94%
“…However, little is known about levels and predictors of mental well-being in various groups of employed mothers. A recent study by the author of the present paper assessed levels and predictors of mental well-being in samples of single and coupled employed mothers in Scandinavia (7). Coupled mothers reported higher levels of mental well-being and lower levels of financial hardship than single mothers.…”
Section: Introductionmentioning
confidence: 94%
“…Single mothers have less access to social support compared with mothers with a partner (see Gähler 1998 for Sweden;Crosier et al 2007 for Australia; for contrary findings on the Scandinavian countries see Bull and Mittelmark 2009). In their study of Sweden and the US, Gunnarsson and Cochran (1990) found that single mothers have smaller social networks than mothers in couples and social networks are positively associated with the individual's health (see e.g.…”
mentioning
confidence: 93%
“…Some research has observed single mothers having higher levels of mental problems than non-single mothers (Whitehead et al, 2000;Fritzell & Burstrom, 2006). A study of single and non-single working mothers in Denmark, Sweden and Norway (Bull & Mittelmark, 2009) shows that financial stress was the most significant predictor of life satisfaction in both groups of working mothers, but also that the level of financial stress is significantly higher for single mothers. Single mothers also scored lower on life satisfaction and happiness.…”
Section: Social Risk Factors For Long-term Sickness Absencementioning
confidence: 99%